Defending Opioid Treatment Agreements: Disclosure, Not Promises - Rager, Joshua B. (The Hastings Center report, 2017)
In order to receive controlled pain medications for chronic non-oncologic pain, patients often must sign a “narcotic contract” or “opioid treatment agreement” in which they promise not to give pills to others, use illegal drugs, or seek controlled medications from health care providers. In addition, they must agree to use the medication as prescribed and to come to the clinic for drug testing and pill counts. Patients acknowledge that if they violate the opioid treatment agreement (OTA), they may no longer receive controlled medications. OTAs have been widely implemented since they were recommended by multiple national bodies to decrease misuse and diversion of narcotic medications. But critics argue that OTAs are ethically suspect, if not unethical, and should be used with extreme care if at all. We agree that OTAs pose real dangers and must be implemented carefully. But we also believe that the most serious criticisms stem from a mistaken understanding of OTAs’ purpose and ethical basis.